Gamification Methods of Game-Based Learning Applications in Medical Competence: A Systematic Literature Review - Hamdi, Lazuardi Fatahilah; Hantono, Bimo Sunarfri; Permanasari, Adhistya Erna (2022)
E-learning implementation can overcome many problems of learning process such as distance, time, and cost. For example, in companies, e-learning can increase the knowledge of employee. E-learning also can be used to improve skills for medical personnel that are important in health care education. Gamification can be implemented by turning the whole learning process into a game by using game elements such as badges, points, levels, and leaderboards in non-game settings to encourage the desired behavior and achievement goals. This study aims to find the implementation of Game-Based Learning Applications in Medical Competence. Using electronic search, we found 5 papers using a mobile application, 2 papers using a desktop application, 10 papers using virtual reality, 5 papers using a web application, and 2 Miscellaneous. All of the papers have environment or media and game-elements to apply gamification. All paper said that gamification can enhance medical competence, but just 7 papers said gamification can increase user attention and motivation and 3 papers said gamification can make user feel challenging and interesting. However, this paper proposes a different way to implement gamification elements. This study shows that gamification is a suitable learning method for medical personnel to improve their knowledge and increase motivation, attention, learning process, and learning outcomes.